Adoption of innovative and evidence-based practices for children and adolescents in state-supported mental health clinics: a qualitative study - Lawrence A. Palinkas; Mee Young Um; Chung Hyeon Jeong; Ka Ho Brian Chor; Serene Olin; Sarah M. Horwitz; Kimberly E. Hoagwood (Health Research Policy and Systems, 2017)
Abstract Background This study examined how mental health clinic administrators decided whether or not to adopt evidence-based and other innovative practices by exploring their views of implementation barriers and facilitators and operation of these views in assessment of implementation costs and benefits. Methods Semi-structured interviews were conducted with 75 agency chief executive officers and program directors of 34 New York State-licensed mental health clinics serving children and adolescents. Results Three interconnected themes relating to barriers and facilitators were identified, namely costs and benefits associated with adoption, capacity for adoption, and acceptability of new practices. The highest percentage of participants (86.7%) mentioned costs as a barrier, followed by limited capacity (55.9%) and lack of acceptability (52.9%). The highest percentage (82.3%) of participants identified available capacity as a facilitator, followed by acceptability (41.2%) and benefits or limited costs (24.0%). Assessment of costs and benefits exhibited several principles of behavioural economics, including loss aversion, temporal discounting use of heuristics, sensitivity to monetary incentives, decision fatigue, framing, and environmental influences. Conclusions The results point to opportunities for using agency leader models to develop strategies to facilitate implementation of evidence-based and innovative practices for children and adolescents.